Identification of novel drug targets in bovine respiratory disease: an essential step in applying biotechnologic techniques to develop more effective therapeutic treatments - Sakharkar MK; Rajamanickam K; Chandra R; Khan HA; Alhomida AS; Yang J (Dove Medical Press, 2018)
Meena Kishore Sakharkar,1 Karthic Rajamanickam,1 Ramesh Chandra,2 Haseeb A Khan,3 Abdullah S Alhomida,3 Jian Yang1 1College of Pharmacy and Nutrition, University of Saskatchewan, Saskatoon, SK, Canada; 2Department of Chemistry, University of Delhi, Delhi, India; 3Department of Biochemistry, College of Science, King Saud University, Riyadh, Saudi Arabia Background: Bovine Respiratory Disease (BRD) is a major problem in cattle production which causes substantial economic loss. BRD has multifactorial aetiologies, is multi-microbial, and several of the causative pathogens are unknown. Consequently, primary management practices such as metaphylactic antimicrobial injections for BRD prevention are used to reduce the incidence of BRD in feedlot cattle. However, this poses a serious threat in the form of development of antimicrobial resistance and demands an urgent need to find novel interventions that could reduce the effects of BRD drastically and also delay/prevent bacterial resistance. Materials and methods: We have employed a subtractive genomics approach that helps delineate essential, host-specific, and druggable targets in pathogens responsible for BRD. We also proposed antimicrobials from FDA green and orange book that could be repositioned for BRD. Results: We have identified 107 putative targets that are essential, selective and druggable. We have also confirmed the susceptibility of two BRD pathogens to one of the proposed antimicrobials – oxytetracycline. Conclusion: This approach allows for repositioning drugs known for other infections to BRD, predicting novel druggable targets for BRD infection, and providing a new direction in developing more effective therapeutic treatments for BRD. Keywords: BRD, pathogenic bacteria, targets, drugs, prioritization, differential genome analyses, druggability